The Present Value of Future Market Power - Cho, Thummim; Grotteria, Marco; Kremens, Lukas; Kung, Howard (Review of Financial Studies, 2026)
We introduce a present-value identity relating a firm’s market value to expected future markups, output growth, discount rates, and investments. Distinguishing current from expected markups reveals five empirical facts: (1) Expected markups account for half the rise in U.S. firm values since 1980. (2) The rise in aggregate expected markups reflects market-share reallocation toward high-expected-markup firms and within-firm increases. (3) Expected markups are linked to intangible investments. (4) They relate negatively to discount rates over time but (5) positively to abnormal returns across firms. Finally, variation in long-term expected markups is primarily associated with asset prices rather than current markups.